Characterisation of Innate Immune and Metabolic Roles of SARM1 in Mouse Macrophages. - Shanahan, Katharine Ann (Trinity College Dublin. School of Biochemistry & Immunology. Discipline of Biochemistry, 2022)
Engagement of the NLRP3 inflammasome in response to injury or infection results in the activation of the pro-inflammatory protease, caspase-1. Cleavage of the caspase-1 substrate, gasdermin D (GSDMD), leads to the GSDMD N-terminal fragment oligomerising and forming plasma membrane pores which facilitates IL-1β release and pyroptosis. The ancient innate immune protein, sterile alpha and HEAT/Armadillo motif-containing protein (SARM1) has been shown to regulate inflammasome outcomes by restricting IL-1β release and augmenting pyroptosis. Given the roles of both GSDMD and SARM1 in cell death and cytokine release following inflammasome activation, this study initially sought to understand how these proteins contributed to both events. Indeed, the generation of Gsdmd-/- cell lines by CRISPR/Cas9 showed that GSDMD was required for cell death and IL-1β release. However, the generation of CRISPR/Cas9 Sarm1-/- macrophages showed that the absence of SARM1 did not alter cell death or cytokine release following NLRP3 inflammasome activation. To clarify the role for endogenous SARM1, the inflammasome phenotype was interrogated in an independent system, namely three independent SARM1-defiicient mice generated by CRISPR/Cas9. Similar to the Sarm1-/- macrophage lines generated, the absence of SARM1 did not uncouple IL-1β release from pyroptosis following NLRP3 inflammasome activation in BMDMs. To gain further insights into SARM1 function, an epitope-tagged SARM1 mouse was generated. In these mice, SARM1 protein expression was confirmed to be detectable in macrophages. Detection of SARM1 in murine macrophages prompted further examination for a role for SARM1 in these cells. SARM1 is the most recently identified NAD+-consuming enzyme. However, the contribution of SARM1 to metabolic pathways linked to NAD+ in macrophages has not yet been explored. Here, it was shown that endogenous SARM1 reduces the reserve capacity of both oxidative phosphorylation and glycolysis, two pathways that are required for generating ATP. Alterations in oxidative phosphorylation were independent of mitochondrial mass and morphology. Instead, cells lacking SARM1 displayed elevated cellular NAD+, complex I activity and mitochondrial membrane potential. Further, in the absence of SARM1, macrophages upregulated glycolysis more efficiently in response to lipopolysaccharide (LPS) stimulation. Increased glycolysis in Sarm1-/- macrophages was accompanied by elevated levels of the pro-inflammatory gene, Il1b, and reduced amounts of the anti-inflammatory gene, Il10, suggesting that SARM1 can limit the inflammatory response. Finally, cleavage of NAD+ by SARM1 generates the calcium mobiliser, cyclic ADPR (cADPR), which is a biomarker of SARM1 activity in neurons and in vivo and may also be important for SARM1 function. Therefore, the ability to monitor changes in cADPR is necessary for studying SARM1. Here, a previously reported spectrophotometric enzymatic cycling assay was established to reliably measure cADPR in macrophages. Using this assay, it was determined that SARM1 is required to generate cADPR in resting murine macrophages, providing evidence that SARM1 has basal enzymatic activity in these cells. Together, this work has clarified the role of endogenous SARM1 in inflammasome activation and uncovered a novel role for SARM1 s NADase activity in mouse macrophages.
APPROVED